'The sight and sound of fireworks' – embodied interactions within piano performance gestures. Issue 1 (2nd January 2018) - Froneman, Anchen
Abstract : Scholarship identifies various technical, expressive, sociocultural and communicative functions of bodily gestures within music performance contexts. The relationships and interactivity of these functions serve the integration of biomechanical activity and the communication of artistic intent underlying music performance. This integration is considered a result of mindful, bodily engagement with a musical instrument in the music-making process. The performer's embodied activity thus translates a particular composition into a musical experience. This article examines and identifies the interactive and interrelated gestural functions of four expert pianists performing Claude Debussy's Feux d'Artifice using Laban/Bartenieff Movement Studies (LBMS). The LBMS concepts of Body, Effort, Space and Shape are utilized not only to identify functional and expressive purposes of gestures during performance, but also the relationships between them and how they serve the unique artistic interpretations of the musical score. This article offers LBMS as an inclusive analytical approach, in combination with an aural analysis of the performance acknowledging score indications, as observational analysis of piano performances informing both embodied knowledges and performance-related practices.